Mistletoe (Viscum album L.) for human papillomavirus: A seven-case series - Nilo E. Gardin; Beatriz Gardin-Machado (Phytomedicine Plus)
Background: Human papillomavirus (HPV) is a significant public health concern, as 50 % of the population are at risk of being infected by this virus at least once in their lifetime. Although the host immune system clears most infections, a small percentage of patients do not fully clear genital HPV. They have an increased risk of developing HPV-associated cancers and can transmit HPV. Currently, no conventional treatments are available to eliminate the virus in HPV carriers. Cases presentation: This study describes the clinical evolution of seven consecutive outpatients with HPV treated with Viscum album extract (VAE). In four patients, the persistence of HPV infection was six months or longer (in two of these patients, it had persisted for 22 months); in three patients, the diagnosis was recent. The patients were treated with topical (vaginal) VAE. For those with high-risk HPV or cervical intraepithelial neoplasia, subcutaneous injections of VAE were administered. Calendula officinalis (vaginal ovules) was prescribed for genital inflammation, and Thuja occidentalis ointment for verrucous lesions. Clinical and laboratory parameters were monitored throughout the treatment. All medications were well tolerated, with only mild skin reactions reported at the VAE injection site. Following treatment, six out of seven patients had negative hybrid capture tests for HPV. One of these six patients required a repeat course of treatment, after which the HPV hybrid capture test turned negative. In one patient, treatment failed to eradicate HPV. Conclusions: Although this case series has a small sample size, there is a therapeutic potential to be further investigated regarding VAE for genital HPV. The treatment needs to be validated by future studies, which should be followed by a clinical trial to rigorously assess the efficacy of mistletoe for genital HPV infection.